Aeromonas hydrophila AHL 0905-2 and Streptococcus agalactiae N14G as Combined Vaccine Candidates for Nile Tilapia - Nunak Nafiqoh; Hessy Novita; Desy Sugiani; Lila Gardenia; Taukhid Taukhid; Arynta Widyaningrum; Dine Resti Susanti (HAYATI Journal of Biosciences, 2022)
In Indonesia, the Nile tilapia (Oreochromis niloticus) is the most widely farmed and available fish for consumption. Production loss due to bacterial infection by Aeromonas hydrophila and Streptococcus agalactiae is the main problem in tilapia cultivation. This study aimed to determine the occurrence of concurrent infection of Aeromonas hydrophila AHL 0905-2 and Streptococcus agalactiae N14G in Nile tilapia based on biochemical and molecular characteristics. From the results of biochemical assay and sequence analysis of the 16S rRNA fragment, Aeromonas hydrophila and Streptococcus agalactiae were confirmed. Genes for aerolysin (417 bp), nuclease (504 bp), lipase (155 bp), and serine protease (211 bp) were found in Aeromonas hydrophila AHL 0905-2, while Streptococcus agalactiae N14G was determined as a 1b serotype group that had genes for CPS L (688 bp), CPSG (621 bp), and CPS J (272 bp). The confirmation in tilapia of Aeromonas hydrophila and Streptococcus agalactiae by PCR and sequencing is important for enabling the detection of these organisms and also for the development of a combined vaccine to tackle co-infection.